Hyphaene compressa; an important palm in the arid and semi-arid regions of Kenya - Omire, Agnes; Neondo, Johnstone; Budambula, Nancy; Gituru, Robert; Mweu, Cecilia Mbithe (Ethnobotany Research and Applications, 2020)
Background: Peasant agroecosystems in Kenya are considered to be a continuum of integrated traditional farming systems and natural ecosystem conservancy programs. Hyphaene compressa (doum palm) exists in arid and semi-arid lands (ASAL) of Kenya. While research in these areas is focusing on new plants to be brought to the areas, there is no focus on doum palm, which is already adapted to these areas. Scanty ethnobotanical knowledge exists in the form of unpublished material. The study aimed to determine domestication status, management practices, important use categories, plant part value, biotic and abiotic stresses of H. compressa. Methods: Four sampling sites in the ASAL of Kenya were selected. Tharaka Nithi, Kwale, Tana River and Turkana. Responses of 79 informants were analyzed to establish doum palm domestication profile, uses, biotic and abiotic stresses affecting its growth. Results: The domestication status varied across the sampled areas, with most regions showing no willingness to domesticate the plant. The study revealed that doum palm has fourteen uses with food (fruit) use, and prevention of soil erosion (roots) recording the highest and the least fidelity level scores, respectively, in the sampled areas. The most observed biotic stress was human interference and pest infestation, while the observed abiotic stress was drought and salinity. Conclusion:The most important doum palm use is food. Due to the high usage and poor domestication, doum palm could be losing its gene pool and hence genetic diversity studies are important for its conservation. Key words: Doum palm, Hyphaene compressa, domestication, ethnobotany, ASAL, conservation, biotic stress, abiotic stress, uses, plant part value